Proceedings of the International Conference on Advances in Energy, Environment and Chemical Engineering 2015
DOI: 10.2991/aeece-15.2015.137
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fatigue and Anti-Hypoxic Effects of Lycium barbarum Polysaccharides

Abstract: Abstract. The purpose of the present study was to evaluate the anti-fatigue and anti-hypoxic effects of Lycium barbarum polysaccharides (LBP) in mice. The mice were randomly divided into four groups, a control group and three treatment groups. The treated groups received different doses of LBP (125, 250 and 500 mg/kg body) by gavage every day for 28 days, while the control group received distilled water. Forced swimming test and normobaric hypoxia test were conducted on the final day of experimentation. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The mechanism of its hypoglycemic effect remains controversy. Previous studies proved that goji extract could increase the liver and muscle glycogen which is the best storage form of glucose [41] . Moreover, LB polysaccharides could enhance the glucose transport in skeletal muscle by facilitating the translocation of glucose transporter 4 (the main insulin sensitive glucose transporter) from the cytoplasm to the cell membrane [42] .…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism of its hypoglycemic effect remains controversy. Previous studies proved that goji extract could increase the liver and muscle glycogen which is the best storage form of glucose [41] . Moreover, LB polysaccharides could enhance the glucose transport in skeletal muscle by facilitating the translocation of glucose transporter 4 (the main insulin sensitive glucose transporter) from the cytoplasm to the cell membrane [42] .…”
Section: Discussionmentioning
confidence: 96%
“…Phytochemical studies have also indicated that the various biological activities of Lycium species are related to their richness in different classes of compounds (e.g., polysaccharides, carotenoids, flavonoids, alkaloids, amides, and terpenoids, among others) (Yao et al, 2011;Qian et al, 2017). Moreover, it has been reported that extracts of plant-based metabolites, especially polysaccharides and vitamins, promote anti-aging, eyesight improvement, and anti-fatigue effects (Wu and Guo, 2015;Yao et al, 2017).…”
Section: Gc-ms Metabolic Profiling Analysismentioning
confidence: 99%